KONTRIBUSI KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH DAN KECERDASAN EMOSIONAL TERHADAP MOTIVASI KERJA GURU SD NEGERI KECAMATAN MANDAILING NATAL - Reni Septrisia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Based on field observations, researchers saw symptoms of the low work ethic of elementary school teachers in Mandailing Natal District and researchers suspected that the low work motivation of teachers was still not good because the situational leadership of principals and teachers still lacked emotional intelligence. The purpose of this study was to determine the contribution of situational leadership and emotional intelligence of the principal to the work motivation of elementary school teachers in Mandailing Natal District. The hypotheses in this study are: (1) principal's situational leadership contributes to teacher work motivation, (2) emotional intelligence contributes to teacher's work motivation, and (3) situational leadership and principal's emotional intelligence jointly contribute to work. motivation of teachers. The research population was elementary school teachers in Mandailing Natal District. Sampling was carried out using Stratified Proportional Random Sampling. Data were collected using questionnaires and rating scales and then analyzed using correlation and regression techniques. The results showed: (1) situational leadership of school principals contributed 21.9% to teacher work motivation, (2) emotional intelligence contributed 16.8% of work to teacher motivation and (3) situational leadership and emotional intelligence of principals jointly contributed amounted to 33.2% of the work of motivated teachers. Based on the above results, it is concluded that the principal factor of situational leadership and teacher emotional intelligence is important to increase teacher motivation in carrying out tasks at school.Keywords: Situational Leadership, Emotional Intelligence, Head, Work Motivation.